Planning a Clinical Trial Programme for Medicinal Products for the Treatment of Axial Spondyloarthritis - D. V. Goryachev (Регуляторные исследования и экспертиза лекарственных средств, 2021)
The criteria for diagnosis and classification of spondyloarthritides (SpAs) have undergone significant changes over the past 10 years. The emergence of new diagnostic methods and availability of new information on the prognosis of the disease outcome made it possible to distinguish a separate group of SpAs—axial SpA. Axial SpA is distinguished as a separate disease due to its high social significance, and special mechanisms of its development. The development of medicinal products for the treatment of axial SpA has some specific features, which requires preparation of specific recommendations for conducting clinical trials of such products. The aim of the study was to elaborate a methodological approach to clinical research and evaluation of efficacy and safety of medicinal products for systemic treatment of axial SpA. The study took into account the requirements/recommendations of the European Medicines Agency for planning clinical trials of medicinal products for the treatment of axial SpA, in order to streamline evaluation of national and foreign clinical trial results. The paper identifies the main stages of clinical trials, and proposes criteria for assessing product efficacy at each stage. It defines methods and tools for assessing clinical trial endpoints, which are necessary for evaluation of treatment effects. The paper describes specific aspects of clinical trial designs and their duration, and identifies the objectives of exploratory and confirmatory clinical trials. It also reviews treatment goals and treatment outcome evaluation. The study results could be used in elaboration of recommendations for clinical research of new medicinal products for axial SpA.